Solve. Good luck! Please do not try to google this.(x^2+x-2)/(6x^2-3x) = √(2x) + (3x^2)/(2)

Answers

Answer 1
Answer: (x^(2) + x - 2)/(6x^(2) - 3x) = √(2x) + (3x^(2))/(2)
(x^(2) + 2x - x - 2)/(3x(x) - 3x(1)) = (2√(2x))/(2) + (3x^(2))/(2)
(x(x) + x(2) - 1(x) - 1(2))/(3x(x - 1)) = (2√(2x) + 3x^(2))/(2)
(x(x + 2) - 1(x + 2))/(3x(2x - 1)) = (2√(2x) + 3x^(2))/(2)
((x - 1)(x + 2))/(3x(2x - 1)) = (2√(2x) + 3x^(2))/(2)
((x - 1)(x + 2))/(3x(2x - 1)) = (2√(2x) + 3x^(2))/(2)
3x(2x - 1)(2√(2x) + 3x^(2)) = 2(x + 2)(x - 1)
3x(2x(2√(2x) + 3x^(2)) - 1(2√(2x) + 3x^(2)) = 2(x(x - 1) + 2(x - 1))
3x(2x(2√(2x)) + 2x(3x^(2)) - 1(2√(2x)) - 1(3x^(2))) = 2(x(x) - x(1) + 2(x) - 2(1)
3x(4x√(2x) + 6x^(3) - 2√(2x) - 3x^(2)) = 2(x^(2) - x + 2x - 2)
3x(4x√(2x) - 2√(2x) + 6x^(3) - 3x^(2)) = 2(x^(2) + x - 2)
3x(4x√(2x)) - 3x(2√(2x)) + 3x(6x^(3)) - 3x(3x^(2)) = 2(x^(2)) + 2(x) - 2(2)
12x^(2)√(2x) - 6x√(2x) + 18x^(4) - 9x^(3) = 2x^(2) + 2x - 4
12x^(2)√(2x) - 6x√(2x) = -18x^(4) + 9x^(3) + 2x^(2) + 2x - 4
6x√(2x)(2x) - 6x√(2x)(1) = -9x^(3)(2x) - 9x^(3)(-1) + 2(x^(2)) + 2(x) - 2(2)
6x√(2x)(2x - 1) = -9x^(3)(2x - 1) + 2(x^(2) + x - 2)
Answer 2
Answer:

Final answer:

To solve the given equation, first simplify both sides. Factor the numerator and denominator on the left side, then solve the quadratic equation obtained.

Explanation:

To solve the given equation:

(x^2+x-2)/(6x^2-3x) = √(2x) + (3x^2)/(2)

First, we need to simplify both sides of the equation. By factoring the numerator and denominator of the left side, we get:

x+22x.

Next, we can simplify the equation further by multiplying both sides by 2x. Finally, we solve the quadratic equation obtained by moving all terms to one side:

2x+4.

Therefore, the solution to the given equation is x = -2.

Learn more about Solving Equations here:

brainly.com/question/17595716

#SPJ12


Related Questions

Write an equation for the line parallel to y = –2x – 5 that contains P(–8, 4).
Sunaina had three pizzas. She shared the pizzas with her friends. Each of them atemany friends ate 3/7 of a pizza. How many friends ate the pizza
Ln(x + 1) − ln(2) = 1
A survey found that 3 out of 100 people have red hair.On the basis of this survey, how many people in a group of 12,000 people are likely to have red hair? A.4000 B.360 C.36 D.3
The formula a= bf-v1 is used to calculate acceleration as the change in velocity over a period of time. Solve the formula for the final velocity, bf in terms of initial velocity, v1, acceleration, a, and time,

9 gal/s=______at/min

Answers

9 gal............................................................1second
?how many gallons......................................60 seconds(1min)

to find out you do 9*60=540 gallons per minute
9 gals/second
xgals/minute
1 minute=60 seconds
xgals/60 seconds=9gals/1 second
x/60=9/1
solve for x
x/60=9/1
x/60=9
multily both sides by 60 to clear fraciton
x times 60/60=9 times 60
x times 60/60=x times 1=x

x=540

the answer is 540 gallons per minute

The question is in the picture.

Answers

Answer:

The third answer choice

Step-by-step explanation:

So sqrt(5)-sqrt(9*5) or sqrt(5)-3sqrt(5). We can rewrite this as -2sqrt5.

Kuta Software - Infinite Algebra 1
Finding Slope from a graph

Answers

what is the question ?

Answer:  

   

Step-by-step explanation:

   

A drug trial had 256 participants. A survey was done to gather information about the participants experiences with side effects.

Answers

Answer:

There is really no solution because the question doesn't look full and cannot be answered without more details.

Find the area of the figure to the nearest tenth.a.

77.9 sq mm

c.

70 sq mm


b.

72.5 sq mm

d.

540 sq mm

Answers

Look at the picture in the attachment.
The area of the figure is equal to the sum of the areas A₁ and A₂.

A_1=9 \ mm * 4.8 \ mm=43.2 \ mm^2 \nA_2=(9 \ mm * 7.7 \ mm)/(2)=(69.3 \ mm^2)/(2)=34.65 \ mm^2 \n \nA=43.2 \ mm^2 + 34.65 \ mm^2=77.85 \ mm^2 \approx 77.9 \ mm^2

The answer is A.

The population of a small town is increasing at a rate of 325 people per year. Write and solve a multiplication equation to find how long it will take the population to increase by 6, 825

Answers

Answer:

21 years

Step-by-step explanation:

For this problem, you only need to divide 6,825 by 325.

6,825/325=21

21 years

I hope that helpful
6.825/325=21 year